Gamificação: modelagem de conteúdos para programas e aplicativos educativos no ambiente da TV digital interativa - Américo, Marcos [UNESP]; Navari, Shelley Costa [UNESP]; Belda, Francisco Rolfsen [UNESP] (My University, 2014)
With the deployment of Digital TV in Brazil, there is a need to foment the development and production of interactive audiovisual quality content, especially for programs that present educational messages from the entertainment concept - defined as Edutertainment. The objective of this study is to propose application of the gamification as a link of communication to encourage and modify user behavior, through a narrative that encourages intrinsic motivation for learning and entertainment in this media. This paper points out that there are few models of screenplays for applications production, particularly educational, with simultaneous interactive applications for television flow or complementary programming content offered. For this reason, a special attention is given to the screenplay, by virtue of inserting in its construction, the elements that make up the mechanics and dynamics of games. As a result, is shown the entry "Gamification-iDTV", which defines these two scenarios, as well as the development of a modeling methodology of a content and process, supported by conceptual maps, wireframes and roadmaps, substantiating the conception and elaboration of screenplay's prototype with elements of gamification for educational programs and its interaction applications.

Com a implantação da TV Digital no Brasil, surge a necessidade de se fomentar a concepção e produção de conteúdos audiovisuais interativos de qualidade que apresentem mensagens educativas a partir do Edutretenimento. Este estudo propõe a aplicação da gamificação como elo comunicacional para incentivar e modificar o comportamento dos usuários, através de uma narrativa que incentive a motivação intrínseca para o entretenimento e o aprendizado nesses meios. Existem poucos modelos de roteiros para a produção de aplicativos, sobretudo educacionais, com aplicações interativas simultâneas para o fluxo televisivo ou para o conteúdo complementar da programação ofertada. Por essa razão, é atribuída uma atenção especial ao roteiro, em virtude de se inserir, em sua construção, os elementos que compõem a mecânica e a dinâmica dos jogos. Como resultado, é apresentado o verbete Gamificação-TVDI , bem como o desenvolvimento de uma metodologia de modelagem de conteúdo e de processo, apoiada em mapas conceituais, wireframes e roadmaps, fundamentando a concepção e a elaboração de um protótipo de roteiro com elementos de gamificação para programas educativos e seus aplicativos de interação.
Gamification: modeling of contents for programs and educative applications in the environment of interactive digital TV
Keywords: Gamification; Screenplay writing; Edutertainment; Educational application; Interactive digital television; Mídia e tecnologia; Interdisciplinar; Gamificação; TV digital; Comunicação social